2011
DOI: 10.1021/ja201951t
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure in Situ 129Xe NMR Spectroscopy and Computer Simulations of Breathing Transitions in the Metal–Organic Framework Ni2(2,6-ndc)2(dabco) (DUT-8(Ni))

Abstract: Recently, we have described the metal-organic framework Ni(2)(2,6-ndc)(2)(dabco), denoted as DUT-8(Ni) (1) (DUT = Dresden University of Technology, 2,6-ndc = 2,6-naphthalenedicarboxylate, dabco = 1,4-diazabicyclo[2.2.2]octane). Upon adsorption of molecules such as nitrogen and xenon, this material exhibits a pronounced gate-pressure effect which is accompanied by a large change of the specific volume. Here, we describe the use of high-pressure in situ (129)Xe NMR spectroscopy, i.e., the NMR spectroscopic measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 88 publications
(141 reference statements)
8
139
0
Order By: Relevance
“…A first application of 129 Xe NMR spectroscopy to MOFs has been reported in 2006 [179]. Subsequently, other authors made use of the favorable properties of 129 Xe NMR in order to study MOFs [23,180,181,182,183]. …”
Section: Solid-state Nmr Spectroscopic Studies Of Host–guest Intermentioning
confidence: 99%
See 1 more Smart Citation
“…A first application of 129 Xe NMR spectroscopy to MOFs has been reported in 2006 [179]. Subsequently, other authors made use of the favorable properties of 129 Xe NMR in order to study MOFs [23,180,181,182,183]. …”
Section: Solid-state Nmr Spectroscopic Studies Of Host–guest Intermentioning
confidence: 99%
“…One way of studying the breathing transitions is by sensing the MOF lattice itself and its changes. Since the breathing transitions change the pores and/or their “entries” if the crystal structure of the MOF changes, these effects can also be explored in an indirect way by using probes like 129 Xe sensing the inner surface of the pores as has been demonstrated for the metal–organic frameworks MIL-53 [182] and DUT-8 [24,183]. …”
Section: Solid-state Nmr Spectroscopic Studies Of Host–guest Intermentioning
confidence: 99%
“…Examples include zeolites 22 as well as a number of different MOFs. [23][24][25][26] FPMD also allows one to model certain electronic properties (e.g., dipole moment of adsorbed molecules 27 ) that are hardly accessible through forcefield-based MD, as well as study chemical reactions, as was recently demonstrated in studies of thermal stability of materials from the IRMOF family. 28,29 FPMD is naturally well-suited to study stimuli-induced deformations and structural transitions in flexible materials, especially when used in the isobaric ensemble to study pressure-and temperature-induced transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Such understanding can either be gained through theory, using first-principles simulations, [8][9][10][11][12][13][14][15][16][17][18] or through experimental probes, such as infrared (IR) absorption and Raman scattering. [8][9][10][11]18,[20][21][22][23][24] Much progress has been made in improving the properties of MOFs. For example, it has been shown that using unsaturated metal centers, such as MOF74 with open Mg, Mn, Zn, Ni, Cu, or HKUST-1 with Cu, results in higher absorption density for hydrogen and faster absorption at small partial CO 2 pressures, the latter of which is highly desirable for CO 2 capturing applications.…”
mentioning
confidence: 99%